Determination of metabolic equivalents during low- and high-intensity resistance exercise in healthy young subjects and patients with type 2 diabetes - Zanuso, S; Bergamin, M; Jimenez, A; Pugliese, G; D’Errico, V; Nicolucci, A; Ermolao, A; Balducci, S (Biology of Sport, 2016)
The purpose of this study was to quantify the metabolic equivalents (METs) of resistance exercise in obese patients with type 2 diabetes (T2DM) and healthy young subjects and to evaluate whether there were differences between sessions executed at low- versus high-intensity resistance exercise. Twenty obese patients with T2DM (62.9±6.1 years) and 22 young subjects (22.6±1.9 years) performed two training sessions: one at vigorous intensity (80% of 1-repetition maximum (1RM)) and one at moderate intensity (60% of 1RM). Both groups carried out three strength exercises with a 2-day recovery between sessions. Oxygen consumption was continuously measured 15 min before, during and after each training session. Obese T2DM patients showed lower METs values compared with young healthy participants at the baseline phase (F= 2043.86; P<0.01), during training (F=1140.59; P<0.01) and in the post-exercise phase (F=1012.71; P<0.01). No effects were detected in the group x intensity analysis of covariance. In this study, at both light-moderate and vigorous resistance exercise intensities, the METs value that best represented both sessions was 3 METs for the obese elderly T2DM patients and 5 METs for young subjects.